The Identity of three Fabrician Chrysidid Species (Hymenoptera) - Lynn Siri Kimsey (Psyche: A Journal of Entomology)
As part of a world revision of the family Chrysididae it has been necessary to borrow or study in situ as many of the oldest types as possible because of potential confusion about their identity. The species described by Fabricius represent a particular problem. He named many of the commonest European species, as well as other less common ones. Although the majority of Fabrician type specimens are still extant, it is clear that the chrysidid types were never seen by most later workers. In several instances the Fabrician species was assumed to be one thing when in fact it belonged to an entirely different genus. One example of this was Chrysis festiva Fabricius, which has always been considered a Pentachrysis, or Chrysis with 5 apical abdominal teeth (Mocsáry 1889, Dalla Torre 1892, Bischoff 1913). However, festiva is actually a species of Parhopes, as discussed by Kimsey (1987). The three species below present similar problems.